2007
DOI: 10.1063/1.2770726
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and crystallization studies of thin amorphous solid water films on Ru(0001) and on CO-precovered Ru(0001)

Abstract: The deposition and the isothermal crystallization kinetics of thin amorphous solid water ͑ASW͒ films on both Ru͑0001͒ and CO-precovered Ru͑0001͒ have been investigated in real time by simultaneously employing helium atom scattering, infrared reflection absorption spectroscopy, and isothermal temperature-programmed desorption. During ASW deposition, the interaction between water and the substrate depends critically on the amount of preadsorbed CO. However, the mechanism and kinetics of the crystallization of ϳ5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 100 publications
4
42
1
Order By: Relevance
“…[18] Finally, at saturation (q CO % 2/3 ML), a (5 ffiffi ffi 3 p 5 ffiffi ffi 3 p )R308 structure was observed by means of He atom scattering (HAS). [24,25] In contrast to CO, hydrogen is adsorbed dissociatively on Ru(0001). Experimental studies found non-activated adsorption in addition to a direct, activated mechanism occurring on a distribution of barriers.…”
Section: Introductionmentioning
confidence: 98%
“…[18] Finally, at saturation (q CO % 2/3 ML), a (5 ffiffi ffi 3 p 5 ffiffi ffi 3 p )R308 structure was observed by means of He atom scattering (HAS). [24,25] In contrast to CO, hydrogen is adsorbed dissociatively on Ru(0001). Experimental studies found non-activated adsorption in addition to a direct, activated mechanism occurring on a distribution of barriers.…”
Section: Introductionmentioning
confidence: 98%
“…The crystallization kinetics will provide information about the properties of supercooled liquid water. A variety of experimental techniques (including desorption, [16][17][18][19][20] physisorption, 11,21-24 infrared spectroscopy, 5,10,[25][26][27][28] and electron microcopy 12,29 ) have been used to study ASW crystallization. The majority of the above mentioned studies report that crystallization occurs via bulk nucleation although a few studies suggest that nucleation may start at the vacuum interface.…”
mentioning
confidence: 99%
“…In the very thinnest films epitaxial growth on the substrate is clearly determinant, as can be seen in work on very thin films of ice ( Kondo et al 2007). As the film thickness increases, the substrate ceases to play a role in the film morphology and the mesoscale morphologies of the structure zone model appear.…”
Section: Discussionmentioning
confidence: 69%